Preliminary observations on the induction of precocious flowering in Hevea brasiliensis by PP333 - Yeang H Y; Samsuddin Z (Journal of Natural Rubber Research, 1986)
The growth retardant PP333, applied as a soil drench, induced precocious flowering in young ungridled Hevea planted in polybags or in the field. Viable pollen and seeds were obtained from the treated plants. Some effects of PP333 on floral and vegetative morphology are described.
Keywords: Hevea brasiliensis; Induction; PP333